Immediate effect of thoracic spinal manipulation versus passive stretching on upper trapezius pain in university students: A randomized controlled trial - Sherin Nada Salsabila; Adnan Faris Naufal (Physical Education and Sports: Studies and Research, 2025)
Background: Pain disorders in the upper trapezius muscle are often experienced by students due to non-ergonomic postures and excessive duration of device use. Interventions such as spinal manipulation and stretching exercises are non-invasive interventions often used to reduce pain and improve muscle function. Objectives: This study compares the effectiveness of two interventions in reducing trapezius muscle pain among university students. Methods: This randomized controlled trial involved 40 physiotherapy students divided equally into two intervention groups. Group I received thoracic spinal manipulation, and Group II received passive stretching. Each intervention was administered in a single 15-minute session. Pain intensity was measured using the Numeric Rating Scale (NRS) before and immediately after treatment. Data were analyzed using the Wilcoxon Signed-Rank test for within-group comparisons and the Mann–Whitney U test for between-group analysis, with an alpha level of 0.05. Results: The Wilcoxon test revealed a significant decrease in pain within both groups (Group I: median pre 4.5 [3.63–5] to post 2.5 [1.50–3.38], p = 0.000, r = 0.879; Group II: median pre 4.25 [3–5] to post 1 [0.13–3], p = 0.000, r = 0.84), indicating a significant effect of both interventions. The Mann–Whitney U test showed no statistically significant difference in pain reduction between the two groups (median pain difference = 2 [1–3] for both, U = 186.5, Z = –0.375, p = 0.707, r = 0.06). Conclusions: Both thoracic spinal manipulation and passive stretching were effective in reducing upper trapezius pain immediately after a single session, but no significant difference was found between the two interventions. These findings suggest that both approaches provide comparable short-term benefits; however, further research with larger samples, multiple sessions, and more extended follow-up periods is needed to confirm their long-term efficacy.